Final Exam

# Final Exam - Version 013 – K Final Exam – gualdani...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Version 013 – K Final Exam – gualdani – (56455) 1 This print-out should have 25 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0 points Find the derivative of f when f ( x ) = 6 x 4 + 4 x 3 + 3 π . 1. f ′ ( x ) = 3 parenleftBig 1 − 2 x 7 x 4 parenrightBig 2. f ′ ( x ) = 12 parenleftBig 2 x 7 + 1 x 4 parenrightBig 3. f ′ ( x ) = 12 parenleftBig 2 x 7 − 1 x 4 parenrightBig correct 4. none of the other answers 5. f ′ ( x ) = 3 parenleftBig 2 x 6 + 1 x 3 parenrightBig 6. f ′ ( x ) = 3 parenleftBig 2 x 6 − 1 x 3 parenrightBig 7. f ′ ( x ) = 12 parenleftBig 1 − 2 x 7 x 4 parenrightBig Explanation: Since d dx ( x r ) = rx r − 1 holds for all r , we see that f ′ ( x ) = 24 x 3 − 12 x 4 . Consequently, f ′ ( x ) = 12 parenleftBig 2 x 7 − 1 x 4 parenrightBig . keywords: derivatives, negative powers 002 10.0 points Find the derivative of f when f ( x ) = (2 − 5 x ) e 3 x +3 . 1. f ′ ( x ) = (11 − 15 x ) e 3 x +3 2. f ′ ( x ) = (11 + 15 x ) e 3 x +3 3. f ′ ( x ) = (6 − 15 x ) e 3 x +3 4. f ′ ( x ) = (1 − 15 x ) e 3 x +3 correct 5. f ′ ( x ) = (1 + 15 x ) e 3 x +3 Explanation: By the Product and Chain Rules, f ′ ( x ) = − 5 e 3 x +3 + 3(2 − 5 x ) e 3 x +3 . Consequently, f ′ ( x ) = (1 − 15 x ) e 3 x +3 . 003 10.0 points Find the derivative of f when f ( θ ) = ln(sin 6 θ ) . 1. f ′ ( θ ) = 6 sin 6 θ 2. f ′ ( θ ) = cot6 θ 3. f ′ ( θ ) = 6 cot6 θ correct 4. f ′ ( θ ) = 6 tan6 θ 5. f ′ ( θ ) = − tan 6 θ 6. f ′ ( θ ) = 1 cos 6 θ Explanation: Version 013 – K Final Exam – gualdani – (56455) 2 By the Chain Rule, f ′ ( θ ) = 1 sin(6 θ ) d dθ (sin 6 θ ) = 6 cos6 θ sin 6 θ . Consequently, f ′ ( θ ) = 6 cot6 θ . 004 10.0 points Find f ′ ( x ) when f ( x ) = x 2 − ln ( 4 + x 2 ) . 1. f ′ ( x ) = 6 x + 2 x 3 (6 + x 2 ) 2 2. f ′ ( x ) = 6 x − x 3 4 + x 2 3. f ′ ( x ) = 2 x − 6 x 3 (4 + x 2 ) 2 4. f ′ ( x ) = 6 x + 2 x 3 4 + x 2 correct 5. f ′ ( x ) = 2 x + 3 x 3 4 + x 2 Explanation: By the Chain Rule, f ′ ( x ) = 2 x − 2 x 4 + x 2 . Consequently, after simplification, f ′ ( x ) = 6 x + 2 x 3 4 + x 2 . 005 10.0 points Determine the derivative of f ( x ) = 2 sin − 1 ( x/ 3) . 1. f ′ ( x ) = 6 √ 1 − x 2 2. f ′ ( x ) = 2 √ 9 − x 2 correct 3. f ′ ( x ) = 3 √ 9 − x 2 4. f ′ ( x ) = 2 √ 1 − x 2 5. f ′ ( x ) = 3 √ 1 − x 2 6. f ′ ( x ) = 6 √ 9 − x 2 Explanation: Use of d dx sin − 1 ( x ) = 1 √ 1 − x 2 , together with the Chain Rule shows that f ′ ( x ) = 2 radicalbig 1 − ( x/ 3) 2 parenleftBig 1 3 parenrightBig . Consequently, f ′ ( x ) = 2 √ 9 − x 2 ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 13

Final Exam - Version 013 – K Final Exam – gualdani...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online